KEPEMIMPINAN KEPALA MADRASAH DALAM MEMBUDAYAKAN AKHLAQUL KARIMAH SISWA DI MADRASAN ALIYAH NEGERI SAMPANG - Nurhadi , Ali; Idris, Hasbiyallah; Asmoni, Asmoni (re-JIEM (Research Journal of Islamic Education Management), 2021)
The leadership of the head of the madrasa is important in managing the madrasa he leads, including the formation of akhlaqul karimah. This research is a qualitative research with a descriptive type that portrays the leadership of the madrasa principal in cultivating akhlaqul karimah in MAN Sampang. There are three research focuses with the following findings. First, the form of civilizing akhlaqul karimah students applied at MAN Sampang is carried out every morning some teachers and BK welcome students who come, while students who enter the MAN Sampang environment will shake hands with the waiting teacher and BK teacher, not precede the teacher who walks in front of him not riding a motorcycle when passing in front of the teacher and madrasa lobby, reading prayers before and after KBM. The two leaderships of the madrasa head participated in carrying out existing policies, including being an example in cultivating good morals towards teachers and students. The three supporting factors in cultivating akhlaqul karimah at MAN Sampang are adequate infrastructure, policies from the madrasa principal, the willingness of the students themselves and the attitude of the education staff who directly meet with students will become role models for students at MAN Sampang.